Suprasellar salivary gland-like pleomorphic adenoma - Kun Yao; Zejun Duan; Yu Bian; Mengyang Wang; Xueling Qi (Wolters Kluwer Medknow Publications, 2014)
Suprasellar salivary gland-Like pleomorphic adenoma is not a common disease and seldom reported so far. We are reporting a case of a 23-year-old man with recurrent suprasellar salivary gland-like pleomorphic adenoma, who underwent an operation of subtotal, subfrontal resection under the wrong pathology diagnosis of benign teratoma in another hospital 4-year-ago. Four years later, he was admitted to our hospital for additional visual loss of the right eye (left, 1.0; right, 0.4) resulting from tumor regrowth. Magnetic resonance imaging revealed that suprasellar extension and compressed optic chiasm resulted in visual disturbance of the patient. The tumor was totally excised and histological examination evidenced the pathological features of intrasellar salivary gland-like pleomorphic adenoma. The patient did not receive any further treatment and he is free from tumor recurrence for 30 months after the operation. From this point of view, clinical prognosis of intrasellar salivary gland-like pleomorphic adenoma was good after total surgical resection.